FORMULATION AND OPTIMIZATION OF LEVAMISOLE CHEWABLE TABLETS - CHAUDHARY, PRADIP KUMAR; T., ABDUL RAHEEM; MACHALE, MANJUNATH U.; VASIA; SADIK, SHAIK (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of the present study was to prepare and optimize levamisole chewable tablets by using various super disintegrants, namely; sodium starch glycolate, DRC Indion 204, and DRC Indion 234. Methods: Drug excipient compatibility study was carried out by FTIR spectroscopy to verify the compatibility of levamisole with the excipients. Nine batches of levamisole chewable tablets were prepared according to 32 factorial designs using a direct compression method by optimizing the super disintegrant concentration. The powder blend was exposed to pre-compression studies of the powder blend followed by post-compression studies of the formulated tablets. Results: FTIR study revealed that the excipients used in the formulations were compatible with the drug. The pre-compression and post-compression parameters were found within the IP limits. Form the dissolution studies, it was evident that the formulation prepared with DRC Indion 234 (50 mg) showed maximum percentage drug release in 45 min (97.13%) hence it is considered as optimized formulation. When compared to all other formulation, the batches with DRC Indion 234 (F7-F9) showed a better release of the drug (90 % drug release within 45 min). Conclusion: Nine batches of levamisole chewable tablets were successfully formulated by optimizing the concentration of super disintegrants such as sodium starch glycolate, DRC Indion 204, and DRC Indion 234. It was concluded from the dissolution studies that the DRC Indion 234 is the best super disintegrant irrespective of their concentration for the formulation of levamisole chewable tablets when compared to sodium starch Glycolate and DRC Indion 204.